A motivational perspective on punishment in social dilemmas. (1st January 2017) - Pfattheicher, Stefan; Keller, Johannes
ABSTRACT: In social dilemma situations, individuals benefit from uncooperative behaviour while exploiting resources of the collective. One prominent solution to prevent uncooperative behaviour and to increase cooperation is to establish a sanction system in that private resources are invested by individuals to punish uncooperative interaction partners. The present review is intended to provide an overview concerning motivational determinants of punishment in social dilemma situations. Specifically, we (a) outline that fairness concerns and revenge motivate individuals to punish uncooperative other individuals, (b) show that this is done especially when they possess the basic motivational orientation of a prevention focus. We (c) illustrate that individuals do not punish to acquire a good reputation in the eyes of others, and (d) elaborate on whether individuals punish to regulate satisfaction. Finally, we present empirically neglected motivational factors in studies on punishment in social dilemmas and discuss limitations and possible future directions in this field of research.